2008
DOI: 10.1021/cm7028036
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Formation of W/Mo-Oxides: A Multidisciplinary Study of Growth and Shape

Abstract: The hydrothermal formation of mixed nanoscale W/Mo-oxides with the hexagonal tungsten bronze (HTB) structure has been investigated by in situ EDXRD (energy dispersive X-ray diffraction). Compared to the binary oxide systems, they display intermediate kinetics with a nucleation-controlled mechanism dominated by the slow growing tungsten component. Furthermore, the thermal stability of nanostructured W/Mo-HTB compounds has been monitored through combined in situ X-ray absorption spectroscopy (XAS) and XRD in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 58 publications
1
52
0
Order By: Relevance
“…6 Moreover, the selection of the adequate alkali cation additives during the hydrothermal process of synthesis, allows both the crystal morphology control as well as the structure stability. 7 In this sense, it has been proposed that the HTB framework cannot be maintained without traces of stabilizing ions or molecules in the hexagonal channels.…”
Section: Wo3mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, the selection of the adequate alkali cation additives during the hydrothermal process of synthesis, allows both the crystal morphology control as well as the structure stability. 7 In this sense, it has been proposed that the HTB framework cannot be maintained without traces of stabilizing ions or molecules in the hexagonal channels.…”
Section: Wo3mentioning
confidence: 99%
“…The existence of h-WO3 with only residual occupation of the hexagonal tunnels 7 and, therefore, with accessible active acid sites, led to the idea of modifying the composition of the structural framework with the addition of vanadium 8 and transform the material into a bifunctional catalyst with acidic and redox properties simultaneously. The efficiency of these materials was tested in the transformation of glycerol to acrylic acid.…”
Section: Wo3mentioning
confidence: 99%
“…This cell also has no water-cooling system because the Kapton window temperature was kept at less than 373 K due to the high thermal conductivity of Al, even at a sample temperature of 703 K. The system can be applied to reaction analysis of solid oxide, bimetallic catalyst for fuel cells, [19][20][21][22] and in situ analysis of W oxide photo/electrochromic materials. 54,55 These powder samples are loaded into a small container made of BN or graphite and fixed to the heater. The cell is thus universally applicable to many systems in the measurements of fluorescence XAFS under the reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[20] This synthetic route can subsequently be tuned by using alkali chlorides as additives in the above-mentioned hydrothermal procedure. [16,21] They exert a dual function: on the one hand, they stabilize the wide interior of the hexagonal channel system through intercalation and on the other hand, the morphology of the products can be steered with the alkali cation. The use of LiCl and NaCl gives rise to nanorod formation, whereas very small nanorods organize into cylinders that furthermore form spherical aggregates in the presence of KCl, RbCl and CsCl (Fig.…”
Section: Materials Synthesis: Hydrothermal Tuning Of Oxide Nanomaterimentioning
confidence: 99%
“…1). [21] Further parameter investigations of the hydrothermal system showed that the formation of the resulting hierarchical W/Mo-oxide architectures depends on the presence of the larger alkali cations K + , Rb + and Cs + . The question how this morphological variety can arise from a single hydrothermal protocol inspired us to investigate the reaction pathway with in situ methods.…”
Section: Materials Synthesis: Hydrothermal Tuning Of Oxide Nanomaterimentioning
confidence: 99%